2005
DOI: 10.1055/s-2005-858819
|View full text |Cite
|
Sign up to set email alerts
|

Perkutane Thermoablation von Nierentumoren

Abstract: Due to modern examination techniques such as multidetector computed tomography and high-field magnetic resonance imaging, the detection rate of renal neoplasms is continually increasing. Even though tumors exceeding 4 cm in diameter rarely metastasize, all renal lesions that are possible neoplasms should be treated. Traditional treatment techniques include radical nephrectomy or nephron-sparing resection, which are increasingly performed laparoscopically. Modern thermal ablation techniques such as hyperthermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 34 publications
0
1
0
2
Order By: Relevance
“…Also, contrary to the transforaminal approach, the interlaminar approach expose more PLL and during endoscopic surgery, heat from radiofrequency (RF) cautery or laser coagulation can cause inflammation. Although irrigation is used throughout such surgery, previous reports on cancer treatment have revealed that the intraoperative RF thermal injury can be significant 30,31,50) . If the pseudocyst's internal space connects with the epidural or extraforaminal space, there are no massive effects or clinical symptoms such as low back pain and/or leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…Also, contrary to the transforaminal approach, the interlaminar approach expose more PLL and during endoscopic surgery, heat from radiofrequency (RF) cautery or laser coagulation can cause inflammation. Although irrigation is used throughout such surgery, previous reports on cancer treatment have revealed that the intraoperative RF thermal injury can be significant 30,31,50) . If the pseudocyst's internal space connects with the epidural or extraforaminal space, there are no massive effects or clinical symptoms such as low back pain and/or leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Verfahren werden vor allem bei Rezidivtumoren mit lokalen Verwachsungen und allgemein schlecht operablen Patienten eingesetzt. Es ist jedoch heute schon klar, dass diese Verfahren auch bei resektablen Patienten eine wertvolle Alternative darstellen [13]. In welchem Umfang diese Verfahren einen Einfluss auf das tumorfreie Überleben der Patienten hat, wird derzeit untersucht.…”
Section: Lokal Begrenzte Tumorenunclassified
“…Minimalinvasive Ansätze zur Tumorbehandlung wie die laserinduzierte Thermotherapie (LITT) [1], Kryoablation [2], Radiofrequenzablation (RFA) [3,4] und thermische Ablation durch Induktionserhitzung [5] nehmen an klinischer Bedeutung zu. Neuere Konzepte versuchen auch den Einsatz von Ferrofluiden in der Tumortherapie zu etablieren [6].…”
Section: Introductionunclassified